Evaluation of High-Alert Drug Storage in The Central Pharmacy of RSUD Ratu Zalecha Martapura: Evaluasi Penyimpanan Obat High Alert di Apotek Sentral RSUD Ratu Zalecha Martapura - Rosanti, Diah Aulia; Sari, Sri Oktaviani; Sari, Sindwi Rinanda; Mahendra, Rachul Ridho; Sandi, Dita Ayulia Dwi; Sari, Okta Muthia; Putra, Aditya Maulana Perdana; Rahmatullah, Satrio Wibowo; Jenah, Rina Astiyani; Hafizah, Noor (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: High-alert drugs require special attention when used because they can cause adverse reactions. High-alert drugs are classified into 3, namely, concentrated electrolytes, LASA, and cytostatics. Objectives: This study aimed to determine the evaluation of High-alert drug storage at the central pharmacy of Ratu Zalecha Martapura Hospital. Material and Methods: The research was conducted using a descriptive method, with observational data collection using an observation checklist sheet. The population and study sample took data on all High-alert medicines at the central pharmacy of Ratu Zalecha Martapura Hospital. Results: High alert drug storage was based on SOP, placed in a central pharmacy using the FIFO and FEFO methods, was placed in a separate place based on cytotoxic drug groups, electrolyte concentrates, and others. High alert drug storage according to storage temperature requirements for each drug (cold temperature and room temperature), was labeled "high alert" and electrolyte concentrates were only available in pharmaceutical installations. Conclusions: The conclusion of this research was High-alert drug storage in the Pharmaceutical installation of Ratu Zalecha Martapura Hospital have been qualified seven (7) criteria based on Minister of Health Decision Nu. 1128 of 2022 and Minister of Health Regulation Nu. 72 of 2016. Good and correct drug storage is very important in order to maintain the quality and quality of drugs.